Quantification of Iridium Dissolution at Water Electrolysis Relevant Conditions Using a Gas Diffusion Electrode Half-Cell Setup - Geuß, Moritz; Löttert, Lukas; Böhm, Thomas; Hutzler, Andreas; Mayrhofer, Karl J.J.; Thiele, Simon; Cherevko, Serhiy (ACS Catalysis, 2024)
Recently, attempts have been made to understand and quantify Ir dissolution in application-relevant single-cell electrolyzers. While obtaining crucial insights, these studies are hindered by intrinsic system complexity and the required labor-intensive microscopic analyses of cross sections of the used catalyst coated membranes. To expand the understanding of dissolution processes in realistic catalyst layers for the oxygen evolution reaction and to accelerate the discovery of dissolution-stable materials, we utilize herein a gas-diffusion type half-cell setup to observe and quantify Ir dissolution at application-relevant conditions. The operation of this setup allows the recording of multiple measurement points for a single electrode throughout an electrochemical protocol and, thus, the monitoring of changes in the dissolution of the Ir-containing catalyst layer over time. The results indicate (I) a temperature-dependent stabilization and activation of the catalyst during conditioning, (II) a beneficial effect on the Ir stability by the application of a protective voltage, and (III) a lower dissolution of Ir from catalyst layers containing rutile IrO2. Therefore, fast benchmarking in a gas-diffusion type setup can accelerate the development of improved dissolution-resistant catalyst layers and aid in developing dissolution-mitigating cell voltage management, which are crucial to achieving significant Ir-loading and cost reduction in proton exchange membrane water electrolysis.
CRIS-Team Scopus Importer:2024-08-02
Keywords: catalyst degradation; gas diffusion electrodes; Ir dissolution; nafion; water electrolysis